Effect of high silicon-aluminum coal ashes on sintering and fusion characteristics of a potassium-rich biomass ash. Issue 5 (October 2020) - Fan, Hongli; Li, Fenghai; Guo, Qianqian; Guo, Mingxi
Abstract: The effects of high silicon-aluminum coal ashes (Shajuzi coal ash (SJZA) and Pingshuo coal ash (PSA)) on the sintering and fusion behaviors of a potassium-rich biomass ash (cotton stalk ash (CSA)) were investigated by a horizontal tube furnace and an ash fusion temperature (AFT) analyzer. X-ray diffraction (XRD), thermogravimetry and differential scanning calorimetry (TG-DSC) techniques were applied to analyze the mineral transformations and thermal behaviors of the ash samples. As the coal ash mass ratio varied from 0 to 50%, the sintering degree of CSA/SJZA and CSA/PSA mixtures gradually mitigated. The AFTs of the two groups of mixtures all presented parabolic with respect to coal ash ratio. The potassium content in CSA was very high (K2 O, 39.55%), and K-containing minerals mainly existed as low melting point (MP) matters, i.e., sylvite (KCl), arcanite (K2 SO4 ), potassium carbonate (K2 CO3 ), and fairchildite (K2 Ca(CO3 )2 ). The mitigation of sintering degree was ascribed to a decrease in KCl content with increasing coal ash ratio. When the coal ash ratio was less than 20%, the decrease in AFT was due to the consumption of alkaline earth metal oxide and the formation of K silicate. The conversions of low MP K salts to high MP K–Al silicates (kalsite (KAlSiO4 ) and nepheline (KNa3 Al4 Si4 O16 )) and the formations of other high MP minerals increased the AFTs after adding 20% coal ash. The thermogravimetric analysis showed that the endothermic peak of KCl evaporation weakened to disappear and the exothermic peaks of some reactions enhanced with rising coal ash ratio. Highlights: Sintering-fusion-property variation mechanism of K-rich biomass ash (CSA) is studied. High silicon-aluminum coal ashes abate the sintering degree of CSA effectively. Ash fusion temperature presents parabolic with respect to coal ash content. Al2 O3 and SiO2 play key role in the sintering-fusion-property regulation of CSA.